The rising challenge of water resources management at the urban fringes - evidence from Ferghana district of Uzbekistan [Abstract only] - Mukhamedova, Nozilakhon; Wegerich, Kai (2014)
With the global expansion of urban areas, competition over both land and water resources is steadily increasing, especially within developing countries(FAO 2012; Kuslu 2007; CER 2009). The expansion of urban areas into agricultural areas, such as in Uzbekistan, has created competition for water between farmers and non-farmers (FAO 2002, 2005). Subsequent growth of urban and peri-urban areas envisages new and expanded demands for water resources, entailing both reproductive and productive uses especially by the poor (Drechsel et al. 2006; van Koppen et al. 2006). The integration of these other, competing uses into the planning or proper design of water provision and management systems has been lacking (van Koppen et al. 2006). The agricultural sector, being the former most dominant sector in the Uzbek Soviet Socialist Republic (SSR) was the core provider of employment and basic livelihoods. After independence in 1991, Uzbekistan experienced a political and economic transition, which resulted in transformation of water land as well as water management and social and institutional challenges, particularly for the agricultural sector. Here a case study on the urbanizing Ferghana district in Uzbekistan is presented which highlights rising competition for water and the associated gender dimensions of the changing water management structure. While traditionally Water User Associations (WUAs) are set up to govern and manage water resources for farmers, the urban expansion into agricultural areas means that WUAs now must integrate the concerns of nonfarmers and multiple water uses in peri-urban communities. Given the expansion and increased importance of kitchen gardens for the majority of the rural population for livelihood security, it is necessary to reprioritize on their respective water needs and towards better integration in WUAs. Donors as well as the government have to adapt their policies, project and recommendations to these changes.